The Effect of Solvent on the Process of Hydrogenation of Cotton Missella - Suvanova Fayoza Usmanovna; Eshankulova Irada Khushnazarovna (Research Parks Publishing LLC, 2021)
The results of the analysis of the content of organosulfur compounds in a low-boiling hydrocarbon solvent obtained from a mixture of oil and gas condensate at a ratio of 1: 1 and the results of studying the kinetics of the hydrogenation process of cotton miscella obtained using traditional extraction gasoline and a new hydrocarbon solvent are presented